Jigsaw Learning Model Assisted by Puzzle Media to Improve Collaboration Skills of Fourth-Grade Elementary School Students - Dewi Puji Lestari; Astri Sutisnawati; Rifky Aditya Ramadhan (Journal of Innovation and Research in Primary Education, 2026)
Low collaborative engagement among elementary students remains a persistent challenge in 21st-century classrooms, where policy frameworks increasingly mandate collaboration as a core graduate competency. This study investigated whether the application of the jigsaw learning model assisted by puzzle media could improve the collaboration skills of fourth-grade students at SDN Cemerlang, Sukabumi, Indonesia.  A Classroom Action Research (CAR) design following the Kemmis and McTaggart spiral model was employed across two instructional cycles with 36 students of class IVB (2025/2026 academic year). Collaboration skills were assessed using a validated questionnaire covering five indicators: cooperation, flexibility, responsibility, compromise, and communication, scored against a four-category rubric. The mean collaboration score improved from 75.5% (Fair) in Cycle I to 82.8% (Good) in Cycle II. All five indicators surpassed the 80% success threshold by the end of Cycle II, with the Compromise indicator recording the largest gain (+7.8 percentage points). These findings confirm that the structured interdependence embedded in the jigsaw model, enriched by the concrete and motivating nature of puzzle media, effectively cultivates multidimensional collaborative competence. The integrated approach offers a replicable, low-resource strategy for developing 21st-century collaboration skills at the elementary level.